PSYCHOLOGICAL FOUNDATIONS OF DEVELOPING COMMUNICATIVE ABILITIES (World Bulletin of Education and Learning, 2026)
This article analyzes the psychological foundations of developing communicative abilities. Particular attention is paid to the stages of psychological development, the mental mechanisms of the communication process, and the role of the socio-psychological environment in shaping students’ communicative skills.
Keywords: Communicative competence, psychological development, social competence, interpersonal communication.